Primary Nutritional Content of Bio-Flocs Cultured with Different Organic Carbon Sources and Salinity - JULIE EKASARI; ROSELIEN CRAB; WILLY VERSTRAETE (Bogor Agricultural University, Indonesia, 2010)
Application of bio-flocs technology (BFT) in aquaculture offers a solution to avoid environmental impact of high nutrient discharges and to reduce the use of artificial feed. In BFT, excess of nutrients in aquaculture systems are converted into microbial biomass, which can be consumed by the cultured animals as a food source. In this experiment, upconcentrated pond water obtained from the drum filter of a freshwater tilapia farm was used for bio-flocs reactors. Two carbon sources, sugar and glycerol, were used as the first variable, and two different levels of salinity, 0 and 30 ppt, were used as the second variable. Bio-flocs with glycerol as a carbon source had higher total n-6 PUFAs (19.1 + 2.1 and 22.3 + 8.6 mg/g DW at 0 and 30 ppt, respectively) than that of glucose (4.0 + 0.1 and 12.6 + 2.5 mg/g DW at 0 and 30 ppt). However, there was no effect of carbon source or salinity on crude protein, lipid, and total n-3 PUFAs contents of the bio-flocs.